Integritas Akademik dalam Membangun SDM Profesional di Perguruan Tinggi: Kasus Academic Dishonesty STIE Perbanas - Adi Susilo Jahja (Universitas Negeri Malang, 2016)
This article reviews the academic integrity at STIE Perbanas based on the case of academic dishonesty having occurred at the institution. Kohlberg's concepts of stages in moral development are used to highlight the case review, indicating the mutual, relationship between lecturers, students, and administrative staff in running a better academic atmosphere. At the end, it is suggested that all the three university elements obey both legal compliance and ethical compliance in their achievement of academic integrity.